The effect of mindfulness training prior to total joint arthroplasty on post-operative pain and physical function: A randomised controlled trial. (October 2019) - Dowsey, Michelle; Castle, David; Knowles, Simon; Monshat, Kaveh; Salzberg, Michael; Nelson, Elizabeth; Dunin, Anthony; Dunin, Jo; Spelman, Tim; Choong, Peter
Highlights: Total joint arthroplastyis the only definitive surgical intervention for treating advanced hip or knee osteoarthritis. Pre-surgery psychological distress is an important predictor of sub-optimal outcomes following TJA. Pre-surgery MBSR© improves pain and function in people with psychological distress undergoing total joint arthroplasty. A potential causal mechanism to explain these findings is yet to be identified. Abstract: Objective: To evaluate the efficacy of Mindfulness-Based Stress Reduction (MBSR) in improving pain and physical function following total joint arthroplasty (TJA). Design: Two-group, parallel-group, randomised controlled trial, conducted between September 2012 and May 2017. Setting: Single centre study conducted at a University-affiliated, tertiary hospital. Intervention: People with arthritis scheduled for TJA, with a well-being score <40 (Short Form-12 Survey) were randomly allocated to a pre-surgery eight-week MBSR program or treatment as usual (TAU). Outcome Measures: Self-reported joint pain and function at 12 months post-surgery, assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Secondary outcomes were knee stiffness and global improvement (WOMAC); physical and psychological well-being (Veterans RAND 12-item Health Survey); self-efficacy (Arthritis Self-Efficacy Scale); and mindfulness (5-Factor Mindfulness Questionnaire). Results: 127 participants were randomised; 65 to MBSR and 62 to TAU, of which 45 participants allocated to the intervention and 56 participants allocated to usual care proceeded to surgery and 100 (99%) completed primary outcome measures. Greater improvements in knee pain (mean difference, -10.3 points, 95% CI -19.0 to -1.6; P  = 0.021) and function (mean difference, -10.2 points, 95% CI -19.2 to -1.3; P  = 0.025) at 12 months post-surgery were observed in the MBSR group compared to the TAU group. A between group difference in global scores (-9.5 points, 95% CI -17.9 to -1.1; P  = 0.027) was also observed. No other differences in secondary outcomes were observed. Conclusion: MBSR improves post-surgery pain and function in people with psychological distress undergoing TJA. Further research is required to examine potential barriers to broader implementation and uptake.